Narasi Visual dan Makna Simbolik Film Pendek “49 Days” - Rico Steffenly Herisen; Yana Erlyana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines how semiotic and visual communication elements are employed in the short film 49 Days to represent psychological trauma rooted in mystical beliefs within the context of a Chinese-Indonesian family. Using a descriptive qualitative method, the research applies Roland Barthes’ semiotic framework and examines cinematographic aspects including symbols, color, lighting, framing, and character blocking. The 22-minute film narrates the story of a young mother who struggles with the loss of her child amid cultural pressures, patriarchal relations, and an authoritarian family structure that limits her freedom. The findings reveal that kitchen tools, clothing colors, confined domestic spaces, and nonverbal gestures function as symbolic markers of inner conflict, social repression, and deep feelings of guilt. Visual strategies such as symmetrical composition, low-key lighting, and the use of enclosed spaces further intensify the sense of isolation, helplessness, and estrangement experienced by the protagonist. The analysis emphasizes that visual signs are not merely aesthetic choices but construct a coherent narrative that uncovers psychological trauma while simultaneously offering cultural critique of mystical beliefs and patriarchal systems. These findings contribute to the academic discourse on visual communication studies and provide practical insights for the development of short film production in Indonesia that is more sensitive to local cultural and social contexts.